Aplicación web para la administración de los materiales almacenados en las bodegas de la empresa constructora Coinfra S.A. - Zambrano Loor, Joel Marcial (2014)
Construction companies, as COINFRA S.A. have high complexity in managing storage and distribution of materials, if that control is not efficient, it is exposed to risk losing time by not having the right stuff at the right time, which can lead to some very significant task of the work that affected the end of delivery work; and secondly, increased costs for loss or impairment of a non- controlled resource. With the design and implementation of a web application and using the MIDAS methodology which enabled the development of web system by phases, giving structure to the development of the application, the first phase was completed to obtain software requirements, in the second phase designing the static part of the application, third database was designed and finally the system functionality was applied. Programs such as MySQL, WAMP Server, Adove Dreamweaver, MySQL Workbench are used; the PHP, Codeigniter, Bootstrap, Grocery CRUD tools to develop software quickly, accurately and practicing. It got the company substantially improve the control and management of goods, materials and tools stored in the hold; since the application can know at any time the location, inventory level and responsible for the movement of these resources , saving time and minimizing costs.